Pelatihan Manajemen Sumber Daya Manusia Tentang Pemanfaatan Sosial Media Dikalangan Bisnis Umkm Kabupaten Bengkulu Tengah - Abdillah, Willy; Zoraya, Intan; Widanti, Afrima; Putri, Lydia Gustina (Jurnal Dehasen Untuk Negeri, 2025)
This Community Service (PKM) activity aims to increase the understanding and skills of MSME players assisted by the Central Bengkulu Regency Cooperative and Small Business Office in human resource management (HR) in the digital era and how MSME Business Actors utilize Banking technology to improve MSME businesses. Micro, Small and Medium Enterprises (MSMEs) are the backbone of the Indonesian economy, contributing around 60% of the Gross Domestic Product (GDP) and absorbing more than 97% of the national workforce (Ministry of Cooperatives and SMEs, 2021). However, many MSMEs face challenges in access to financing and technology. This research aims to develop MSMEs through the utilization of digital banking technology and advance micro businesses by providing KUR Mikro loan facilities. Using quantitative and qualitative approaches, this study will analyze the impact of digital technology on MSME performance and the effectiveness of the KUR Mikro program in improving the competitiveness of micro enterprises.